A case–control study of prevalence of anemia among patients with type 2 diabetes. (December 2016) - Antwi-Bafour, Samuel; Hammond, Samuel; Adjei, Jonathan; Kyeremeh, Ransford; Martin-Odoom, Alexander; Ekem, Ivy
Abstract Background Anemia is defined as a reduction in the hemoglobin concentration of blood, which consequently reduces the oxygen-carrying capacity of red blood cells such that they are unable to meet the body's physiological needs. Several reports have indicated that anemia mostly occurs in patients with diabetes with renal insufficiency while limited studies have reported the incidence of anemia in people with diabetes prior to evidence of renal impairment. Other studies have also identified anemia as a risk factor for the need for renal replacement therapy in diabetes. Understanding the pathogenesis of anemia associated with diabetes may lead to the development of interventions to optimize outcomes in these patients. The aim of this study was therefore to determine the prevalence of anemia among patients with type 2 diabetes. Methods A total of 100 (50 with type 2 diabetes and 50 controls) participants were recruited for our study. Participants' blood samples were analyzed for fasting blood glucose, full blood count and renal function tests among others. The prevalence of anemia was then determined statistically. Results A high incidence of anemia was observed in the cases. Of the patients with diabetes, 84.8 % had a hemoglobin concentration that was significantly less (males 11.16±1.83 and females 10.41±1.49) than the controls (males 14.25±1.78 and females 12.53±1.14). Renal insufficiency determined by serum creatinine level of >1.5 mg/dL, estimated glomerular filtration rate <60 ml/minute/1.73 m2, and erythropoietin levels was also observed to be high in the cases (54.0 %; with mean creatinine concentration of 3.43±1.73 and erythropoietin 6.35±1.28 mIU/mL). A significantly increased fasting blood glucose, urea, sodium, potassium, and calcium ions were observed in the cases (7.99±1.30, 5.19±1.99, 140.90±6.98, 4.86±0.53 and 1.47±0.31 respectively) as compared to the controls (4.66±0.54, 3.56±2.11, 135.51±6.84, 4.40±0.58 and 1.28±0.26 respectively). Finally, a significant association between hemoglobin concentration and fasting blood glucose was also observed in the cases. Conclusions The findings suggest that a high incidence of anemia is likely to occur in patients with poorly controlled diabetes and in patients with diabetes and renal insufficiency.